2010
DOI: 10.1007/s00198-010-1455-3
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic drugs and the risk of hip or femur fracture: a population-based case–control study

Abstract: SummaryThe effect of dopaminergic medication on the risk of hip/femur fractures is not clear. Our results showed a nearly twofold increased risk of hip/femur fractures in current dopaminergic drug users. Concomitant use of antidepressants further increased this risk. Fracture risk assessment may be warranted in elderly users of dopaminergic drugs.IntroductionDopaminergic drugs, often used in the treatment of Parkinson’s disease, have several pharmacological effects that may increase or decrease the risk of fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
1
21
1
3
Order By: Relevance
“…The predisposition for hip fractures in PD may reflect the nature of the falls themselves in that they are often in a sideways or backward direction 2931 Elderly subjects with a rapid gait are more likely to fall forward while those with a shuffling gait tend to fall backward or to the side and suffer a hip fracture 4142 Lower BMD levels at the hip may also contribute to the excess rate of hip fractures in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predisposition for hip fractures in PD may reflect the nature of the falls themselves in that they are often in a sideways or backward direction 2931 Elderly subjects with a rapid gait are more likely to fall forward while those with a shuffling gait tend to fall backward or to the side and suffer a hip fracture 4142 Lower BMD levels at the hip may also contribute to the excess rate of hip fractures in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…44 Alongside a possible deleterious effect on BMD, levodopa improves some motor deficits in PD but tends not to improve postural stability, meaning that patients are potentially more mobile but are perhaps at an increased risk of falls. Side effects of levodopa such as orthostatic hypotension, visual hallucinations and excessive daytime somnolence can further increase risk of falls 41. Levodopa can also induce hyperhomocysteinemia which has been reported as a potential risk factor for fractures 45.…”
Section: Discussionmentioning
confidence: 99%
“…The association between fracture and Parkinson’s disease may be because falls are common among these patients [14]. Koller et al [18] reported that 38% of Parkinson’s disease patients reported falls and 13% fell more than once a week; these patients may have reduced sunlight exposure and a lower dietary intake of calcium and vitamin D. The use of dopaminergic drugs in many Parkinson’s disease patients has also been shown to be a contributory factor to fracture risk [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Another report of similar finding was that of van den Brand et al [ 55 ] who found that current use of both SSRIs and TCAs increased hip or femur fracture risk. Arbouw et al [ 56 ] also found that current use of dopaminergic drugs (1–30 days before the index date) was associated with an increased risk of hip or femur fractures, but the risk rapidly decreased to baseline levels when treatment was discontinued for more than 1 year. Another reason for the discrepancy in results is that we only examined HF, whereas most of previous studies investigated all fractures.…”
Section: Discussionmentioning
confidence: 99%